ASAS-SSR Triennnial Reproduction Symposium: Looking Back and Moving Forward—How Reproductive Physiology has Evolved: Fetal origins of impaired muscle growth and metabolic dysfunction: Lessons from the heat-stressed pregnant ewe1. (26th April 2018) - Yates, Dustin T; Petersen, Jessica L; Schmidt, Ty B; Cadaret, Caitlin N; Barnes, Taylor L; Posont, Robert J; Beede, Kristin A
Abstract: Intrauterine growth restriction (IUGR ) is the second leading cause of perinatal mortality and predisposes offspring to metabolic disorders at all stages of life. Muscle-centric fetal adaptations reduce growth and yield metabolic parsimony, beneficial for IUGR fetal survival but detrimental to metabolic health after birth. Epidemiological studies have reported that IUGR-born children experience greater prevalence of insulin resistance and obesity, which progresses to diabetes, hypertension, and other metabolic disorders in adulthood that reduce quality of life. Similar adaptive programming in livestock results in decreased birth weights, reduced and inefficient growth, decreased carcass merit, and substantially greater mortality rates prior to maturation. High rates of glucose consumption and metabolic plasticity make skeletal muscle a primary target for nutrient-sparing adaptations in the IUGR fetus, but at the cost of its contribution to proper glucose homeostasis after birth. Identifying the mechanisms underlying IUGR pathophysiology is a fundamental step in developing treatments and interventions to improve outcomes in IUGR-born humans and livestock. In this review, we outline the current knowledge regarding the adaptive restriction of muscle growth and alteration of glucose metabolism that develops in response to progressively exacerbating intrauterine conditions. In addition, we discuss the evidence implicating developmental changes in β adrenergic and inflammatory systems as key mechanisms for dysregulation of these processes. Lastly, we highlight the utility and importance of sheep models in developing this knowledge.